The effect of target transparency on managers’ target setting decisions - Arnold, Markus C.; Artz, Martin; Tafkov, Ivo D. (Accounting, Organizations and Society, 2024)
This study investigates, via two experiments, the effects of target transparency, which reflects employees' knowledge about each other's targets in an organization, on managers' target setting decisions. We also investigate whether this effect depends on the need for help among employees. We predict and find that target transparency and need for help interact to influence managers' target setting decisions. Target transparency increases target levels when the need for help is low, but not when it is high. Further, target transparency leads managers to differentiate less between individual employee targets. This reduction is greater when the need for help is high than when it is low. Additional analyses support our theory by revealing that managers strategically set targets in a way that is consistent with an intention to motivate both effort at the individual level and help among employees when such are needed. Our results help explain anecdotal evidence of why companies that value help among employees often make targets transparent throughout the entire organization.